Counterinsurgency in crisis Britain and the challenges of modern warfare - Ucko, David H.; Egnell, Robert (Columbia studies in terrorism and irregular warfare, 2013)
By juxtaposing the deterioration of situations from the Iraq War against Britain's celebrated legacy of counterinsurgency, this investigation identifies both the contributions and limitations of traditional tactics in such settings, exposing a disconcerting gap between ambitions and resources, intent and commitment